A Comprehensive Information Technology System to Support Physician Learning at the Point of Care. (January 2015) - Cook, David A.; Sorensen, Kristi J.; Nishimura, Rick A.; Ommen, Steve R.; Lloyd, Farrell J.
<x xml:space="preserve">Abstract</x> MayoExpert is a multifaceted information system integrated with the electronic medical record (EMR) across Mayo Clinic's multisite health system. It was developed as a technology-based solution to manage information, standardize clinical practice, and promote and document learning in clinical contexts. Features include urgent test result notifications; models illustrating expert-approved care processes; concise, expert-approved answers to frequently asked questions (FAQs); a directory of topic-specific experts; and a portfolio for provider licensure and credentialing. The authors evaluate MayoExpert's reach, effectiveness, adoption, implementation, and maintenance. Evaluation data sources included usage statistics, user surveys, and pilot studies. As of October 2013, MayoExpert was available at 94 clinical sites in 12 states and contained 1, 368 clinical topics, answers to 7, 640 FAQs, and 92 care process models. In 2012, MayoExpert was accessed at least once by 2, 578/3, 643 (71%) staff physicians, 900/1, 374 (66%) midlevel providers, and 1, 728/2, 291 (75%) residents and fellows. In a 2013 survey of MayoExpert users with 536 respondents, all features were highly rated (≥ 67% favorable). More providers reported using MayoExpert to answer questions before/after than during patient visits (68% versus 36%). During November 2012 to April 2013, MayoExpert sent 1, 660 notifications of new-onset atrial fibrillation and 1, 590 notifications of prolonged QT. MayoExpert has become part of routine clinical and educational operations, and its care process models now define Mayo Clinic best practices. MayoExpert's infrastructure and content will continue to expand with improved templates and content organization, new care process models, additional notifications, better EMR integration, and improved support for credentialing activities.